PENGARUH LINGKUNGAN KERJA, PENGETAHUAN DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DI CV. PERDANA MULIA DESA CARINGIN KULON KECAMATAN CARINGIN KABUPATEN SUKABUMI: Manajemen sumberdaya manusia - Dadang Suparman, S.Pd.I., MM (Ekonomedia, 2020)
Employees or employees are the most important in determining the forward and backward of a company. To achieve company goals required employees who are in accordance with the requirements in the company and must also be able to carry out the tasks that have been determined by the company. The purpose of this study was to analyze the effect of work, knowledge and workload on employee performance at CV. Perdana Mulia Caringin Kulon Village, Caringin District, Sukabumi Regency. The population taken in this study were 120 people, the sample used was 55 respondents. This study uses primary data, namely data in the form of a questionnaire (list of questions) given to respondents to be filled in and returned to the researcher. The data obtained were then analyzed using Multiple Linear Regression Analysis. The results of the regression analysis show that the significance of F = 0.000 < (0.05) means that the work environment variable (X1), knowledge (X2) and workload (X3) together have an influence on employee performance (Y). Work environment variable (X1) with a significance of 0.315 which means that partially there is no significant effect on employee performance variables, knowledge variable (X2) with a significance of 0.006 which means partially significant influence on employee performance variables, workload variable (X3) with significance amounting to 0,000 which means partially significant effect on employee performance variables. From the results of linear regression analysis, it is known that the workload variable (X2) is greater in the value of the beta coefficient, so the workload variable (X2) is the independent variable which dominantly affects the variables that affect employee performance at CV. Perdana Mulia.